SPECIFIC FEATURES THE SYNTACTIC ORGANIZATION OF INTERNET DISCOURSE - Abdalieva, Gulistan Rafikovna; Akhymbetov, Sultanbek Duysenbaevich (SCIENCE and SOCIETY, 2026)
The article examines the syntactic features of internet communication, defines the role and functions of ellipsis and parcellation in the syntactic structure of utterances.